2012
DOI: 10.1111/j.1464-410x.2012.11084.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ‐preserving surgery for penile cancer: description of techniques and surgical outcomes

Abstract: • Penile-preserving surgery can achieve good penile cancer control with minimal morbidity and reduced psychosexual side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 11 publications
(17 reference statements)
0
35
0
Order By: Relevance
“…The five-year cancer-specific survival rate following local recurrence was 92% in two large studies (1,6). In addition, sexual function, micturition and cosmetic results were generally well maintained following conservative surgery (3,(6)(7)(8)(20)(21)(22)(23). Accordingly, the use of PSS has risen dramatically at tertiary care centers and has been recommended by certain guidelines, including the European Association of Urology (EAU) Guidelines Group on Penile Cancer, as a standard surgical approach (11-13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The five-year cancer-specific survival rate following local recurrence was 92% in two large studies (1,6). In addition, sexual function, micturition and cosmetic results were generally well maintained following conservative surgery (3,(6)(7)(8)(20)(21)(22)(23). Accordingly, the use of PSS has risen dramatically at tertiary care centers and has been recommended by certain guidelines, including the European Association of Urology (EAU) Guidelines Group on Penile Cancer, as a standard surgical approach (11-13).…”
Section: Discussionmentioning
confidence: 99%
“…This change has been driven by an improved understanding of the biology of the disease (4), quality improvements in pathological evaluation and continuous refinements of surgical techniques (5). PSS has been previously reported to produce excellent cosmetic and functional results without sacrificing oncological outcomes in certain patients with early-stage penile tumors (3,(6)(7)(8)(9). Accordingly, an organ-sparing approach has been recommended for patients with stage T1 disease, according to the 2009 TNM clinical and pathological classification system (10), in national and international guidelines (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Brown C. T. et al in their study of five men with squamous cell carcinoma of glans penis performed subtotal resection of glans and showed that with preservation of distal urethra, spraying of urine observed with total glansectomy can be reduced. At a mean follow-up of 12 months, no recurrence was noted with good cosmetic and functional outcome [34].…”
Section: Glansectomymentioning
confidence: 87%
“…Glansectomy can be done either partially or totally for dealing with local excision of distal tumors on the glans and prepuce (32)(33)(34)(35). This is followed by frozen sections from the cavernosal bed and urethral bed to confirm negative margins followed by an end-shaft urethrostomy.…”
Section: Glansectomymentioning
confidence: 99%
See 1 more Smart Citation